O reconto de Angela-Lago: uma leitura de palavras e imagens, em João Felizardo, o rei dos negócios e Sua Alteza a Divinha - Oliveira, Ana Paula Gualter de (2010)
Based on the literary project of the books João Felizardo, O Rei dos Negócios (Cosac Naify, 2007) and Sua Alteza A Divinha (RHJ, 1990), by Angela-Lago, this dissertation discusses the quality of her work, in its originality, recounted through the act of adaptation. The discussion embraces the literary resultants of junction and fusion of verbal and imagistic language in the infantile literature, revisiting the style and the function of illustration in the light of works written by Heinrich Wölfflin and Luís Hellmeister de Camargo and others distinguished writers. Some theorists and their particular points of view about the literary production by Angela-Lago, such as Rosemary Giudilli Cordioli, Mirta Glória Fernández, Renata Nakano, André Mendes and the author s works, they are applied to the sounding of two versions, which take as a challenge to awake the imaginary of the reader behind of adaptation of canonicals tales of oral tradition. Chapter I recaptures the history of origins of infantile literature, its beginning in Brazil and it shows theories about illustration, communication, imaginary and oral tradition. The study pretends to show new short cuts in the developing of infantile literature for arriving to the object public, the reader-child. Chapter II centralizes in analyze of the book João Felizardo, o rei dos negócios. Based in some concepts about illustration by Wölfflin, it approves the esthetic quality in the illustrated infantile book originated from the junction of verbal and no-verbal languages. Chapter III concentrates in analyze of the book Sua Alteza a Divinha. Based in the essays of Cordioli and Mendes, it refers also the esthetic quality in the book originated from the inter-relation word and image. The dissertative purpose shows that infantile illustrated books develop an imagistic and graphic project of illustration concomitant and interdependent of narrative project of fairy tale of the oral tradition in the adaptation by Angela-Lago writer